Management Accounting Strategies for Environmental Cost Control and Performance Optimization in Green Manufacturing Companies - Eko Cahyo Mayndarto; Olinda da Cruz Alves; Lana Sularto (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Manufacturing firms increasingly face pressure to manage environmental costs from regulations and societal expectations, yet traditional cost accounting methods focusing on labor and materials are inadequate for these challenges. This research aims to explore and propose effective managerial accounting strategies for environmental cost control in green manufacturing firms, highlighting their role in optimizing both operational and financial performance. A qualitative research approach, utilizing secondary data from reputable academic and professional sources, is employed. The study reveals that integrating environmental management accounting tools such as activity-based costing, life cycle costing, and target costing for green design enables firms to better manage environmental costs, leading to improved efficiency and profitability. Furthermore, the study identifies contextual factors, including organizational culture, leadership, and technological capacity, which play significant roles in enhancing the effectiveness of environmental cost control strategies. By incorporating environmental accounting into strategic decision-making, companies can reduce inefficiencies, optimize resources, and align sustainability with financial success. This research provides both theoretical and practical contributions to the field of green manufacturing, offering recommendations for firms to integrate sustainability into their accounting systems to support long-term environmental and economic goals.